Fintech Innovation and Bank Efficiency in Indonesia - Liga Maryunita; Irwan Tri Nugroho (UIN Sunan Gunung Djati, 2022)
This study intends to determine the impact of fintech adoption on the efficiency of conventional banks in Indonesia between 2013 and 2019. The population of this study consisted of all conventional banks listed on the Indonesia Stock Exchange (IDX) between 2013 and 2019, whilst the sample consisted of 38 conventional banks selected using the purposive sampling technique. This study employs two analyses: Data Envelopment Analysis (DEA) to measure bank efficiency and panel data regression analysis to test the hypothesis of the effect of fintech adoption on commercial banks in Indonesia in 2013-2019 using the Stata program. According to the findings of this research, fintech appears to have a positive and discernibly noticeable impact on the operational efficiency of banks. The greater the number of fintech facilities offered by banks, the greater their efficiency; therefore, banks must strengthen innovation and bank infrastructure in order to implement fintech.